A reduced-complexity compressed sensing channel estimation for underwater acoustic channel - Xuan YU; Xuan GENG (Dianxin kexue)
Aiming at the sparse characteristics of underwater acoustic channels for shallow seas, a reduced-complexity look-ahead backtracking orthogonal matching pursuit (RC-LABOMP) channel estimation algorithm was proposed.Firstly, two types of support sets of orthogonal matching pursuit and subspace pursuit channel estimation algorithms were calculated, and then prior information based on the intersection and union of the two support sets were preprocessed.At last, the preprocessed prior information was used to complete look-ahead backtracking orthogonal matching pursuit channel estimation.The preprocessed prior information leads to the decrease of the iteration number of original LABOMP, and reduction of the atom index range, thus the proposed algorithm can reduce the computational complexity of original LABOMP significantly.In addition, combining the proposed algorithm with the underwater acoustic Turbo equalization system is more suitable for underwater acoustic communication systems.Simulation results show that the proposed algorithm demonstrates high estimation accuracy and low bit error rate performance under both conditions of random channels and underwater acoustic channels.It also reduces the computational complexity of the LABOMP algorithm.Therefore, it is an effective method for shallow seas underwater acoustic channels estimation algorithm.